The Effect of Employee Performance on The Quality of Drug Delivery Services in XYZ Hospital Bandung - Ririt Sundari; Tiris Sudrartono (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This research aims to determine how significant the impact of employee performance is on the quality of drug delivery services; the sample and research are 100 patients at XYZ Hospital as respondents who responded to the questionnaire statement, after which quantitative and qualitative analyses were carried out. Information on equation testing shows that the T-count value is 6.239, while with = 5%, the T-table value is 1.987. It means T-count > T-table (6, 239 > 1.987). It means that the Employee Performance variable has an influence significant to the variable of Service Quality. The coefficient of determination (R^2) is 0.284. The influence of employee performance on service quality is 28.4%, and the remaining 71.6% is influenced by other variables not examined.